Tree Diversity Analysis and Study of Minor Forest Products of Tree species of a Tropical Forest Patch of Purulia, West Bengal, India. - Jana, Susanta; Mahapatra, Bingshati Singha; Mallick, Shyamal Kanti (Indian Forester, 2025)
The present paper deals with the phytosociological analysis of the tree species of Nanna Forest patch of Purulia District, West Bengal, India. It is the scientific record of tree diversity in recent time from this unexplored Geographical area, recorded 37 tree species belonging to 23 families including exotic species. The highest Important value Index (IVI value- 36.54) was recorded for the dominant tree species Shorea robusta Gaertn., associated with Madhuca longifolia var. latifolia (Roxb.) A. Chev. (31.25), and Diospyros melanoxylon Roxb. (25.20), Diversity index (H), Dominance index(CD) and Evenness index (E) were calculated from total sample. The value of the indices is 1.56, 0.059, 0.011 respectively. The physicochemical parameter indices soil of the forest region is lateritic in nature. On the basis of IVI value, the forest type is Shorea-Madhuca-Diospyros.